(untitled) (Nativa, 2024)
This study aimed to characterize the formation of surface crusts of arid soil (Typical Torrifluvents) of an alluvial plain in eight locations of Basra Province, in the southern region of Iraq. The unique and intriguing morphological and chemical characteristics were studied with an exceptional level of precision using a scanning electron microscope, ensuring the reliability and accuracy of the results. The crusts were identified as structural crust, puffy crust and salt crust, with thicknesses of 1.0-3.0; 0.5-1.5; and 0.2-0.4 cm, respectively. The depositional environment, particularly the kinetic energy of rainfall, plays an active role in the formation of structural crusts. The swollen crusts occurred in different spatial locations in small hills with cores. These areas are in the form of hills with coverings resulting from the processes of capillary rise of salts and the effect of the processes of evaporation and condensation of water, which leads to an increase in the size of the salt crystal embedded in the construction of these crusts. The salt crusts appeared in interconnected layers as relatively medium-sized crystals resulting from the evaporation of salt solutions in small lakes after rainfall; in this case, they appeared as fine salt crystals in areas affected by capillary rise. The size of the crystals depends on the purity of the salt and the evaporation rate of the salt solution. Scanning Electron Microscopy (SEM) showed that the structural crusts appeared as layers between the closely packed layers of the microplate structure, and the pores were very fine or narrow. The salt crusts showed very small salt crystals, and the crystal size is affected by the purity of the salt in the brine. Keywords: soil crusts; soil porosity; raindrop pressure; infiltration; water evaporation, southern Iraq. Características químicas e morfológicas das crostas em solos sedimentares usando microscópio eletrônico de varredura RESUMO: Estudo objetivou caracterizar a formação das crostas superficiais do solo árido (Torrifluventes Típicos), de uma planície aluvial em oito locais da Província de Basra, na região Sul do Iraque. As características morfológicas e químicas foram estudadas usando um microscópio eletrônico de varredura. As crostas foram identificadas como crosta estrutural, crosta fofa e crosta de sal, com espessuras de 1,0-3,0; 0,5-1,5; e 0,2-0,4 cm, respectivamente. O ambiente deposicional tem um papel ativo na formação de crostas estruturais, além do papel da energia cinética da chuva, cujo efeito é superficial nessas crostas. As crostas inchadas ocorreram em diferentes localizações espaciais, na forma de pequenas colinas com núcleos. Essas áreas estão na forma de colinas com coberturas resultantes dos processos de ascensão capilar de sais e do efeito dos processos de evaporação e condensação da água, o que leva a um aumento no tamanho do cristal de sal imbutido na construção dessas crostas. As crostas de sal apareceram em camadas interconectadas como cristais, de tamanho relativamente médio, resultantes da evaporação de soluções de sal em pequenos lagos após a chuva; nesse caso, elas apareceram como cristais finos de sal em áreas afetadas pela ascensão capilar. O tamanho dos cristais depende da pureza do sal e da velocidade de evaporação da solução de sal. A Microscopia Eletrônica de Varredura (MEV) mostrou que as crostas estruturais apareceram na forma de camadas entre as camadas compactadas da estrutura de microplacas, e os poros eram muito finos ou estreitos. As crostas de sal apresentaram cristais de sal muito pequenos, e o tamanho do cristal é afetado pela pureza do sal na salmoura. Palavras-chave: crostas de solo; porosidade do solo; pressão das gotas de chuva; infiltração; evaporação da água, sul do Iraque.